Memperkuat Perlindungan Pekerja Outsourcing: Analisis Implementasi Kebijakan - Habibi, Nugroho; Amrizal, M. Dio Rhiza; Rozikin, Irkham Syahrul; Ahmad, Iqbal Faza (Sahabat Akademia Group, 2024)
This study aims to provide an overview and address the challenges associated with the implementation of labor protection policies for outsourcing workers in Indonesia. Employing a qualitative approach with a descriptive method, the research delves into a comprehensive and in-depth examination, supported by a literature review. The study's recommendations include reinforcing supervision and law enforcement by actively monitoring outsourcing activities to strengthen oversight and ensure rule enforcement. Implementing stringent measures against outsourcing companies that frequently disregard administrative sanctions by applying penalty rules, such as fines, is also proposed. Enhancing transparency in agreements or Memoranda of Understanding (MoU) between primary companies and outsourcing firms and improving data collection processes are crucial aspects of the recommendations. Beyond policy suggestions, the study aspires to contribute insights to fortify Government Regulations post the enactment of Law No. 6 of 2023. Proposed enhancements involve strengthening operational permit requirements for establishing outsourcing companies by introducing a deposit component, seeking association recommendations for outsourcing companies during the permit application process, specifying sectors for outsourcing, and regulating the technical improvement of outsourcing workers' skills.